KEPENTINGAN EKONOMI DAN POLITIK ARAB SAUDI MENGAKUISISI NEWCASTLE UNITED FC MELALUI PUBLIC INVESTMENT FUND (PIF) PADA TAHUN 2021 - Pramana, Haykal; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study discusses the economic and political interests of Saudi Arabia in acquiring Newcastle United FC through the Public Investment Fund (PIF) in 2021. PIF is used by the Saudi Arabian government to diversify the national economy in line with Saudi Vision 2030. The research method used is a qualitative method with data collection techniques through literature studies sourced from several books, journals, articles, and websites. This study uses the perspective of Liberalism and the theory of Foreign Direct Investment (FDI). The study shows that from an economic perspective, acquisitions are part of Saudi Arabia's strategy to increase revenue from the non-oil and gas sector. From a political perspective, this acquisition allows Saudi Arabia to build a positive image in the eyes of the international community. Keywords: Economic Interests, Political Interests, Saudi Arabia, Public Investment Fund, Newcastle United FC, Saudi Vision 2030.